Identificación del impacto psicosocial en los trabajadores de la educación por Sars-coV-2 en dos colegios Públicos de Bogotá. (2020)
Objective: To identify the psychosocial aspects with the greatest impact on education workers by Sars-coV-2 in two public schools in Bogotá D.C. Methodology: The research has a mixed approach, that is, it combines the qualitative and quantitative approach, an exploratory-descriptive study. Results: It was not possible to use the tool designed by the Ministry of Labor of Colombia, and the tool of the Ministry of Labor of Ecuador was used. In the 8 dimensions, it was found that most of the educators perceived a low risk after adapting to the new normal, however in the dimensions of work load and rhythm, recovery, other important risks were evidenced, in which it is important to generate Corrective and preventive measures that allow comfort to the workers and improve the perception of these, of the previous dimensions to which greater emphasis should be given is dimension 2 development of the competences that speaks of the demands, demands and opportunities with which workers count on to grow in the professional field, without diminishing the importance of the other dimensions.